What Comes First Metacognition or Negative Emotion? A Test of Temporal Precedence - Capobianco, Lora; Heal, Calvin; Bright, Measha; Wells, Adrian (Frontiers in Psychology, 2019)
The Self-Regulatory Executive Function model predicts that emotional symptoms and metacognition causally affect each other, but crucially for the model metacognition can cause emotion disorder symptoms. Therefore, in time-series data involving repeated measurements, metacognitions should predict subsequent changes in emotion. 265 participants completed a questionnaire battery three times over a two month period. Structural equation modelling using cross-lagged panel analysis tested the inter-relationships between metacognitive beliefs, anxiety and depression symptoms over time. The cross-lagged structural model was a significantly better fit than the autoregressive model. Metacognitive beliefs were found to predict subsequent symptoms of anxiety while symptoms of anxiety predicted later metacognition over different time courses. The metacognition factor representing uncontrollability and danger of thoughts appeared to be prominent in the effects observed. Metacognitions and depression were also positively related over time to a lesser degree, but in the cross-lagged model these temporal relationships were non-significant This is likely due to low levels of depression within the sample and low variability over time. The findings for anxiety are consistent with the S-REF model and with experimental and prospective studies supporting metacognitive beliefs as a causal mechanism in psychological distress symptoms.